Effective project management : traditional, agile, extreme - Wysocki, Robert K. (Indianapolis, Indiana : Wiley Pubishing, Inc., 2012)
Expert guidance on ensuring project success--the latest edition! Many projects fail to deliver on time and within budget, and often-poor project management is to blame. If you're a project manager, the newest edition of this expert and top-selling book will help you avoid the pitfalls and manage projects successfully
Includes bibliographical references (p. 719-727) and index
Keywords: Project management